PROSES PENGAMBILAN KEPUTUSAN ADOPSI INOVASI BUDIDAYA MELON (Cucumis melo L.) BERBASIS TEKNOLOGI GREENHOUSE DI ANAGATA FARM KECAMATAN PASAWAHAN KABUPATEN PURWAKARTA - Syabena, Muhammad Farrel; Sarah Sakinah Umadi (Innofarm : Jurnal Inovasi Petanian, 2025)
Melon is widely cultivated in Indonesia due to its promising economic prospects and short cultivation period. This study aims to analyze the process of adopting greenhouse innovation for melon cultivation at Anagata Farm, Purwakarta Regency, West Java, as a solution to the impacts of climate change, thereby improving the production of high-quality melons. The research used a qualitative approach through observation, in-depth interviews, and a case study design. The study focuses on the stages of the innovation adoption decision-making process. The results show that the greenhouse innovation adoption process consisted of five main stages. In the knowledge stage, farmers acquired information from direct visits and social media. In the persuasion stage, farmers evaluated the greenhouse innovation as being more economical and practical. During the decision stage, farmers decided to adopt the greenhouse innovation for melon cultivation. In the implementation stage, they began applying the greenhouse and more advanced cultivation technologies. Finally, in the confirmation stage, farmers continued to adopt the greenhouse innovation to enhance the yield and quality of their produce. Keywords: Adoption; Greenhouse; Innovation; Melon